Anomalies of the Craniocervical Junction (Chiari Malformations) - Giugno, Andrea; Fichera, Valeria; Zanghì, Antonio; Vecchio, Michele; Catalano, Marco; Palmucci, Stefano; Belfiore, Giuseppe; Lavalle, Salvatore; Polizzi, Agata; Praticò, Andrea D. (Journal of Pediatric Neurology, 2024)
Arnold Chiari malformations include a combination of posterior fossa, hindbrain, and cervical occipital junction abnormalities, sometimes associated with spinal cord abnormalities such as spina bifida, syringomyelia, and syringobulbia. The most frequent form is Chiari I syndrome but two other variants, progressively more severe, have been described. Chiari malformations are the result of defective development of posterior fossa and can be due to genetic mutations, skeletal malformations, and intrautero factors. Clinical manifestations depend on the compression of the nerve structures within the foramen magnum and the spinal canal and mainly consist in headache or neck pain, gait disturbances, sensory or motor abnormalities, and autonomic signs. However, a high number of cases of Chiari I is asymptomatic and the diagnosis is occasional. Diagnosis is performed through nuclear magnetic resonance imaging of the brain and cervical tract, although other investigations may support the diagnosis. First-line treatment for candidate patients is a surgical procedure that involves decompression of the posterior cranial fossa and the craniocervical junction, as well as correction of associated malformations with techniques that depend on the severity of the case. Anyhow, some symptomatic patients benefit from conservative medical treatment with nonsteroidal anti-inflammatory drugs.
Keywords: craniocervical junction; Chiari; malformation; genetics; surgery